CORRELATION BETWEEN DURATION AND SITTING POSITION WITH THE INCIDENCE OF LOWER BACK PAIN DURING ONLINE LEARNING - Ahyana, Ahyana; Nurhidayah, Irfanita; Amalia, Riski; Kamal, Anda (E-Jurnal Medika Udayana, 2023)
Low back pain is a musculoskeletal disorder that is very common and has an impact on socioeconomic, individual, family, and community losses. Low back pain is choking between the 12th thoracic rib and the bottom of the gluteal fold, with or without pain radiating down the leg. Since the coronavirus disease 2019 (COVID-19) outbreak hit Indonesia, learning that has been carried out in schools and university has become online learning where learning uses laptops or cell phones with internet facilities and in a prolonged sitting position. The condition of sitting for a long time is the most common posture performed during online learning, so it can cause discomfort and pain in the lower back. This study aimed to determine the correlation between duration and sitting position with the incidence of back pain during online learning. This study used a descriptive correlational method with a cross-sectional design. The sample in this study was 203 students of the Faculty of Nursing at Syiah Kuala University. The data collection technique used a valid and reliable Sitting Position Duration (DPD) questionnaire with a Cronbach's Alpha value of 0.729 and the Nordic Body Map (NBM) questionnaire to see low back pain. This study showed no significant relationship between sitting duration and back pain ( p-value = 0.625 ), sitting duration, and buttock pain ( p-value = 0.616 ). A significant relationship exists between sitting position and back pain ( p-value = 0.002 ) and sitting position and buttock pain ( p-value = 0.001 ). It was concluded that an unergonomic sitting position for a long time could cause low back pain